Out in the Wild: Shawna Dempsey and Lorri Millan’s Lesbian National Parks and Services - Valadares, Desiree (RACAR : Revue d'art canadienne / Canadian Art Review, 2025)
As a performance duo, Winnipeg’s Shawna Dempsey and Lorri Millan have received international accolades for Lesbian National Parks and Services, a multifarious, multi-year performance piece begun in 1997. “In full uniform as Lesbian Rangers,” they travel to various locales such as festivals and parks to “challenge the general public’s ideas of tourism, recreation, and the ‘natural environment.’” While in Banff, Alberta, the duo created a map of the townsite with fictional heritage landmarks to assert a queer presence through humour, satire and play. Dempsey and Millan also create installations, publications and videos, including several components of Lesbian National Parks and Services, such as their 2002 PSAs, Endangered Species, featuring lesbians in decline. In 2018, the Rangers participated in an exhibition by Young Joon Kwak at the Banff Centre for Arts and Creativity entitled The Cave. In an interview with both artists in the fall of 2023 over Zoom, we discussed Canada’s national parks as contested landscapes through the lens of queer ecologies, homosexuality, nature, and visibility while also featuring the evolution of their collaborative performance practice as Lesbian Rangers, and thirty-eight years creating a range of other live, video, and book works.